Pedagogical Skill Activity - Yuldashev Ikhlas Nurmetbayevich (Peerian Journals Publishing, 2022)
All fields have their own pedagogues. But there are not many skilled pedagogues. What does a skilled pedagogue look like, what is pedagogical skill, and what is the actual process of pedagogical activity? You can find out the answers to such questions as well as the scientific ways of becoming a skilled pedagogue by reading this article.
Keywords: Pedagogue; subject; creativity; methods